2010
DOI: 10.17796/jcpd.35.2.9061h7g718834017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mineral Trioxide Aggregate as an Apical Plug in Non-Vital Young Permanent Teeth: Preliminary Results

Abstract: Purpose: The purpose of this study was to evaluate the efficacy of Mineral trioxide aggregate (MTA) clinically and radiographically as material used to induce root end closure in nonvital permanent teeth with immature apices (apexification) in children. Methods: The study included 30 non vital young permanent,single rooted teeth of 22 children between 8 and 13 years of age. Treatment followed a standard non-surgical root canal treatment protocol and the root canal was filled with a apical plug of 4-5 mm of MTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 2 publications
1
10
2
1
Order By: Relevance
“…The use of calcium hydroxide in the short term does not negatively affect tooth resistance 30 . In our case, X-rays after six months of treatment has shown significant decrease in periapical lesions, being in agreement with studies of Annamalai & Mungara 28 and Sarris et al 31 . However, the latter suggest broader clinical trials to evaluate long term success.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The use of calcium hydroxide in the short term does not negatively affect tooth resistance 30 . In our case, X-rays after six months of treatment has shown significant decrease in periapical lesions, being in agreement with studies of Annamalai & Mungara 28 and Sarris et al 31 . However, the latter suggest broader clinical trials to evaluate long term success.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Torabinejad et al 27 have reported antimicrobial properties of MTA for 5 out of 9 facultative bacteria more commonly found in infected root canals, however with no effect on strictly anaerobic bacteria. Annamalai & Mungara 28 have also reported 100% clinical and radiological success rate with MTA in the 12 th month of follow-up, while root extremity closing was observed in 86.6% of cases with root growth in just 30% of cases. In our case, the combination of calcium hydroxide was used as intracanal drug for 15 days to obtain a dry and infection-free canal.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Two types of MTA are available, Grey and white. White MTA was preferred in this case since it is associated with the development of cementoblasts and keratinocytes [8], [9]; though both prove to be good in many perforation cases.…”
Section: Discussionmentioning
confidence: 98%
“…Esta barrera puede estar compuesta por dentina, cemento, hueso, u osteodentina. Para obtener el estímulo necesario para la formación de la barrera apical deben ser colocados materiales inductores dentro del conducto radicular (8,9). Este protocolo de tratamiento no debe confundirse con apicogénesis, que es el tratamiento de un diente vital, cuyo objetivo principal es estimular el desarrollo fi siológico de la raíz y la formación del ápice (10).…”
Section: Apexifi Cación Con Renovación Periódica De Micunclassified